A phase I study of binimetinib (MEK 162), a MEK inhibitor, plus carboplatin and pemetrexed chemotherapy in non-squamous non-small cell lung cancer. (July 2021) - Fung, A.S.; Graham, D.M.; Chen, E.X.; Stockley, T.L.; Zhang, T.; Le, L.W.; Albaba, H.; Pisters, K.M.; Bradbury, P.A.; Trinkaus, M.; Chan, M.; Arif, S.; et al.
Highlights: Recommended phase II dose is binimetinib 30 mg BID with carboplatin/pemetrexed in non-squamous NSCLC. Manageable toxicities observed with the combination of carboplatin, pemetrexed and binimetinib. Objective response rate 50 % and disease control rate 83.3 % with chemotherapy plus binimetinib. Abstract: Introduction: MEK inhibition is a potential therapeutic strategy in non-small cell lung cancer (NSCLC). This phase I study evaluates the MEK inhibitor binimetinib plus carboplatin and pemetrexed in stage IV non-squamous NSCLC patients (NCT02185690). Methods: A standard 3 + 3 dose-escalation design was used. Binimetinib 30 mg BID (dose level 1 [DL1]) or 45 mg BID (dose level 2 [DL2]) was given with standard doses of carboplatin and pemetrexed using an intermittent dosing schedule. The primary outcome was determination of the recommended phase II dose (RP2D) and safety of binimetinib. Secondary outcomes included efficacy, pharmacokinetics, and an exploratory analysis of response based on mutation subtype. Results: Thirteen patients (6 DL1, 7 DL2) were enrolled: 7 KRAS, 5 EGFR, and 1 NRAS mutation. The RP2D was binimetinib 30 mg BID. Eight patients (61.5%) had grade 3/4 adverse events, with dose limiting toxicities in 2 patients at DL2. Twelve patients were evaluated for response, with an investigator-assessed objective response rate (ORR) of 50% (95% CI 21.1%-78.9%; ORR 33.3% by independent-review, IR), and disease control rate 83.3% (95% CI 51.6%-97.9%). Median progression free survival (PFS) was 4.5 months (95% CI 2.6 months–NA), with a 6-month and 12-month PFS rate of 38.5% (95% CI 19.3%-76.5%) and 25.6% (95% CI 8.9%-73.6%), respectively. In an exploratory analysis, KRAS/NRAS -mutated patients had an ORR of 62.5% (ORR 37.5% by IR) vs. 25% in KRAS/NRAS wild-type patients. In MAP2K1 –mutated patients, the ORR was 42.8%. Conclusion: The addition of binimetinib to carboplatin and pemetrexed appears to have manageable toxicity with evidence of activity in advanced non-squamous NSCLC.